Does financial performance moderate the effect of CEO characteristics and stakeholder influence on corporate social responsibility in Indonesia? - Agustina, Lidya; Sudibyo, Yvonne Augustine (Technium Business and Management, 2022)
This study aims to examine the effect of CEO characteristics and stakeholder involvement on CSR disclosure quality, with firm performance as a moderating variable. This study was conducted with the assumption that the analysis of human factors (in this case management) is often forgotten when analyzing CSR reporting. Thus, the upper echelon theory is used as the basis in this study. This study also provides a different measurement of CEO education, where CEO education is not only seen from the background of economic and business education, but also seen from the CSR certification followed by the CEO. The study’s findings, based on data from Kompas-100 firms listed on the Indonesia Stock Exchange from 2018 to 2019, show that CEO tenure, CEO education, and stakeholder involvement all have a significant positive influence on CSR disclosure quality. However, CEO compensation has no effect on CSR disclosure quality. Furthermore, the firm’s financial performance was proven to moderate the positive influence between CEO tenure and CEO education on the quality of the firm’s CSR disclosure, but failed to moderate the effect of CEO compensation and stakeholder involvement on the quality of the firm’s CSR disclosure.